2021
DOI: 10.3390/en14051403
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hydroxylated Multi-Walled Carbon Nanotubes on the Properties of Peg-Cacl2 Form-Stable Phase Change Materials

Abstract: Calcium ions can react with polyethylene glycol (PEG) to form a form-stable phase change material, but the low thermal conductivity hinders its practical application. In this paper, hydroxylated multi-walled carbon nanotubes (MWCNTs) with different mass are introduced into PEG1500·CaCl2 form-stable phase change material to prepare a new type of energy storage material. Carbon nanotubes increased the mean free path (MFP) of phonons and effectively reduced the interfacial thermal resistance between pure PEG and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…In order to produce a new type of energy storage material by Zheng et al, hydroxylated multi-walled carbon nanotubes (MWCNTs) of different mass were incorporated into the PEG1500•CaCl2 form-stable phase change material. They present ideas to the literature for the preparation and application of form-stable phase change materials with high thermal conductivity [52]. We observed that the phase change and thermal conductivity values of the PS-PEG copolymers we synthesized in this study were as high as in these studies.…”
Section: Thermal Conductivitymentioning
confidence: 54%
“…In order to produce a new type of energy storage material by Zheng et al, hydroxylated multi-walled carbon nanotubes (MWCNTs) of different mass were incorporated into the PEG1500•CaCl2 form-stable phase change material. They present ideas to the literature for the preparation and application of form-stable phase change materials with high thermal conductivity [52]. We observed that the phase change and thermal conductivity values of the PS-PEG copolymers we synthesized in this study were as high as in these studies.…”
Section: Thermal Conductivitymentioning
confidence: 54%
“…However, PEG-CaCl 2 /CCF PCMs have no obvious leakage and their shapes remain intact, which is mainly attributed to the complex cross-linking network structure of PEG and CaCl 2 and the network structure adsorption and network barrier of CCF. (1) PEG reacts with CaCl 2 to form the cross-linking structure . At this time, PEG is equivalent to forming a large three-dimensional network structure, and almost all PEG molecules become a part of this network; that is, PEG is forbidden in the macromolecular structure of PEG-CaCl 2 , thus ensuring the shape stability of PCMs.…”
Section: Resultsmentioning
confidence: 99%
“…Phase change materials (PCMs) are innovative materials that efficiently absorb and release a significant amount of energy during phase transformation, serving for temperature regulation and energy storage 29–31 . Polyethylene glycol (PEG) is a well‐known kind of PCMs, which emerges as a highly promising solid–liquid PCM due to its exceptional qualities, such as low vapor pressure, excellent chemical and thermal stability, appropriate phase transition temperature, lack of supercooling, and nontoxic nature 32–34 . PEG also exhibits some drawbacks which would limits its practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31] Polyethylene glycol (PEG) is a well-known kind of PCMs, which emerges as a highly promising solid-liquid PCM due to its exceptional qualities, such as low vapor pressure, excellent chemical and thermal stability, appropriate phase transition temperature, lack of supercooling, and nontoxic nature. [32][33][34] PEG also exhibits some drawbacks which would limits its practical applications. The thermal conductivity of PEG leads to reduced heat transfer efficiency, prolonged heat absorption and release time for PCM, and diminished the corresponding energy storage efficiency.…”
Section: Introductionmentioning
confidence: 99%